1995
DOI: 10.1021/bi00024a020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Asp258 as the Metal Coordinate of Pigeon Liver Malic Enzyme by Site-Specific Mutagenesis

Abstract: Pigeon liver malic enzyme was inactivated by ferrous sulfate in the presence of ascorbate. Manganese and some other divalent metal ions provided complete protection of the enzyme against the Fe(2+)-induced inactivation. The inactivated enzyme was subsequently cleaved by the Fe(2+)-ascorbate system at Asp258-Ile259, which was presumably the Mn(2+)-binding site of the enzyme [Wei, C. H., Chou, W. Y., Huang, S. M., Lin, C. C., & Chang, G. G. (1994) Biochemistry 33, 7793-7936]. For identification of Asp258 as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
7
32
0
Order By: Relevance
“…In pigeon liver malic enzyme, a Fe2+-ascorbate system inactivates the enzyme by cleavage at the peptide bond between Asp"' and Ile259 (Wei et al, 1997). Moreover, site-directed mutagenesis has confirmed that Aspz5' is one of the ligands of Mn" (Wei et al, 1995). Our results suggest that this consensus aspartate, and thus consensus site, plays the same role of metal-binding site not only in all malic enzymes but also in all malolactic enymes.…”
Section: Comparison Of Malic and Malolactic Enzymessupporting
confidence: 62%
See 1 more Smart Citation
“…In pigeon liver malic enzyme, a Fe2+-ascorbate system inactivates the enzyme by cleavage at the peptide bond between Asp"' and Ile259 (Wei et al, 1997). Moreover, site-directed mutagenesis has confirmed that Aspz5' is one of the ligands of Mn" (Wei et al, 1995). Our results suggest that this consensus aspartate, and thus consensus site, plays the same role of metal-binding site not only in all malic enzymes but also in all malolactic enymes.…”
Section: Comparison Of Malic and Malolactic Enzymessupporting
confidence: 62%
“…The functions of these sites have been intensively studied in malic enzymes by different enzymic methods and by site-directed mutagenesis (Chang et al, 1993;Gavva et al, 1991 ;Wei et al, 1995Wei et al, , 1997. The consensus box 111 was exactly identical between malic and all malolactic enzymes.…”
Section: Comparison Of Malic and Malolactic Enzymesmentioning
confidence: 99%
“…Without a three-dimensional crystal structure available, affinity cleavage at the putative metal-binding site by the metal-catalyzed oxidation system (MCO) 1 may be the optimal approach of reaching the above goal. Using this technique with the Fe 2ϩ -ascorbate system, Asp 258 is successfully identified in our previous study as one of the metal-binding sites (Wei et al, 1994), as confirmed by site-directed mutagenesis (Wei et al, 1995). In that study, some divalent metal ions were found to be capable of providing protection of the enzyme against Fe 2ϩ -induced inactivation.…”
Section: Cytosolic Malic Enzyme ((S)-malate:nadpmentioning
confidence: 71%
“…12,35,36 The other metal ligands include a water molecule and the 2-hydroxyl group of L-malate. 34 L-malate was proposed to bind with the enzyme through a metal bridge, which serves as an electrophile in the activation of a substrate.…”
Section: Discussionmentioning
confidence: 99%